2011
DOI: 10.3390/cancers3022014
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-Targeting as a Biological Therapy: Understanding Nimotuzumab’s Clinical Effects

Abstract: Current clinical trials of epidermal growth factor receptor (EGFR)-targeted therapies are mostly guided by a classical approach coming from the cytotoxic paradigm. The predominant view is that the efficacy of EGFR antagonists correlates with skin rash toxicity and induction of objective clinical response. Clinical benefit from EGFR-targeted therapies is well documented; however, chronic use in advanced cancer patients has been limited due to cumulative and chemotherapy-enhanced toxicity. Here we analyze differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 68 publications
(64 reference statements)
1
31
0
1
Order By: Relevance
“…Previous studies have reported that various factors, such as genetic mutations and nonoptimal administration of EGFR antagonists, may influence the direct effects of EGFR- targeted therapies on overall survival 19,29. Perhaps future studies examining the impact of nimotuzumab on survival in greater detail are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that various factors, such as genetic mutations and nonoptimal administration of EGFR antagonists, may influence the direct effects of EGFR- targeted therapies on overall survival 19,29. Perhaps future studies examining the impact of nimotuzumab on survival in greater detail are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…18 The antibody has also been extensively evaluated in the clinical setting in patients bearing advanced head and neck, glioma, lung, esophageal, pancreatic, and gastric cancer, among others. 19,20 Nimotuzumab currently has marketing approval for the treatment of advanced head and neck, glioma, and esophageal cancer patients in combination with irradiation or chemo-radiotherapy. More than 40 000 patients have been treated with nimotuzumab worldwide as part of clinical trials or after marketing approval in 33 countries.…”
Section: Introductionmentioning
confidence: 99%
“…More than 40 000 patients have been treated with nimotuzumab worldwide as part of clinical trials or after marketing approval in 33 countries. [19][20][21] Apart from other EGFR antagonists, nimotuzumab does not induce severe skin rash or hypomagnesemia. 22,23 This paper describes the results of the use of nimotuzumab in a single institution, the Calixto García Hospital, which is among the biggest teaching hospitals in Havana and one of the nationwide reference institutions for neurosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although nimotuzumab is not included in the 12 antibodies which have been approved by the Food and Drug Administration (FDA), its use would be interesting because of the absence of side effects such as skin rashes [3,10]. This is in contrast to the use of other of monoclonal antibodies targeting EGFR which cause skin rashes in every use [11,12].…”
mentioning
confidence: 82%